2019
DOI: 10.1136/bmj.l344
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour at 41 weeks versus expectant management until 42 weeks (INDEX): multicentre, randomised non-inferiority trial

Abstract: Objective To compare induction of labour at 41 weeks with expectant management until 42 weeks in low risk women. Design Open label, randomised controlled non-inferiority trial. Setting 123 primary care midwifery practices and 45 hospitals (secondary care) in the Netherlands, 2012-16. Participants 1801 low risk women with an uncomplicated singleton pregnancy: rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 43 publications
7
78
10
2
Order By: Relevance
“…One cohort study of 51 473 women found an increase in labour dystocia after induction of labour was performed at 41 GW (RR=1.29, 95% CI 1.22 to 1.37)35 while a randomised trial of 508 women found no difference (RR 0.55, 95% CI 0.20 to 1.45) 36. Conflicting results have been published regarding induction of labour and risk of CS 2 37 38. In this study, no change in the CS trend was found, despite the substantial increase in induction of labour.…”
Section: Discussioncontrasting
confidence: 73%
“…One cohort study of 51 473 women found an increase in labour dystocia after induction of labour was performed at 41 GW (RR=1.29, 95% CI 1.22 to 1.37)35 while a randomised trial of 508 women found no difference (RR 0.55, 95% CI 0.20 to 1.45) 36. Conflicting results have been published regarding induction of labour and risk of CS 2 37 38. In this study, no change in the CS trend was found, despite the substantial increase in induction of labour.…”
Section: Discussioncontrasting
confidence: 73%
“…This review identified four RCTs relevant to these timeframes and concluded that there was insufficient evidence to support IOL at 41 weeks instead of 42 weeks. A recent RCT not included in these systematic reviews compared IOL at 41 weeks with EM until 42 weeks found that IOL was associated with reduced adverse perinatal outcomes (1.7% vs 3.1%, absolute risk difference, -1.4%, 95% CI -2.9 to 0.0), however, this study was underpowered to demonstrate superiority of IOL at 41 weeks [35].…”
Section: Post-term Pregnancymentioning
confidence: 79%
“…There were 15 studies related to IOL for post-term pregnancy (> 40 weeks). These included a Cochrane review [6], a systematic review [34], an RCT [35], a prospective cohort study [36], nine retrospective cohort studies [37][38][39][40][41][42][43][44][45], and two secondary analyses of cohort studies [46,47]. The Cochrane review assessed the effects of a policy of IOL at or beyond term compared with a policy of awaiting spontaneous labour (or until planned birth is deemed necessary) on maternal and neonatal outcomes [6].…”
Section: Post-term Pregnancymentioning
confidence: 99%
“…Two previous trials have made the same comparisons as SWEPIS; the first, from Turkey, recorded one death, in the expectant management group 4. The second, the INDEX (INDuction of labour at 41 weeks with a policy of EXpectant management until 42 weeks) trial, found a reduced risk of adverse perinatal outcomes in favour of induction, and the study recorded one perinatal death in the induction group compared with two in the expectant management group 5…”
mentioning
confidence: 98%